2023
DOI: 10.1186/s40249-023-01132-w
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of chlorfenapyr-based net Interceptor® G2 against pyrethroid-resistant malaria vectors from Cameroon

Magellan Tchouakui,
Riccado F. Thiomela,
Elysee Nchoutpouen
et al.

Abstract: Background The increasing reports of resistance to pyrethroid insecticides associated with reduced efficacy of pyrethroid-only interventions highlight the urgency of introducing new non-pyrethroid-only control tools. Here, we investigated the performance of piperonyl-butoxide (PBO)-pyrethroid [Permanet 3.0 (P3.0)] and dual active ingredients (AI) nets [Interceptor G2 (IG2): containing pyrethroids and chlorfenapyr and Royal Guard (RG): containing pyrethroids and pyriproxyfen] compared to pyrethr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The low mortality response obtained with the pyrethroid-only net could be associated to pyrethroid resistance driven by CYP6P9a/b as previously reported in this strain 27,28 and the An funestus from Malawi 43 . The greater e cacy of the CFP-based net observed in this study as previously reported in Benin, Tanzania, and Cameroon 24,44,45 should be therefore attributed to the potential bioactivation of chlorfenapyr by P450s in pyrethroid-resistant mosquitoes. Interceptor® G2 could be therefore an e cient replacement for pyrethroid-only ITNs for the reduction of malaria transmission malaria vectors as observed in Benin and Tanzania 19,46 .…”
Section: Chlorfenapyr-based Tools Are Turning Mosquito Molecular Defe...supporting
confidence: 56%
See 1 more Smart Citation
“…The low mortality response obtained with the pyrethroid-only net could be associated to pyrethroid resistance driven by CYP6P9a/b as previously reported in this strain 27,28 and the An funestus from Malawi 43 . The greater e cacy of the CFP-based net observed in this study as previously reported in Benin, Tanzania, and Cameroon 24,44,45 should be therefore attributed to the potential bioactivation of chlorfenapyr by P450s in pyrethroid-resistant mosquitoes. Interceptor® G2 could be therefore an e cient replacement for pyrethroid-only ITNs for the reduction of malaria transmission malaria vectors as observed in Benin and Tanzania 19,46 .…”
Section: Chlorfenapyr-based Tools Are Turning Mosquito Molecular Defe...supporting
confidence: 56%
“…These insecticide chemistries have been presented as good alternatives as they have different mechanism of actions and unique targets 17,18 . Interceptor G2 net treated with alpha-cypermethrin and chlorfenapyr is one example of a long-lasting dual insecticide mixture net that has shown great promise at controlling pyrethroid-resistant malaria vectors in randomised cluster control trials conducted in Benin and Tanzania [19][20][21] and several experimental hut trials across the continent [21][22][23][24] . The new insecticide formulation combining the neonicotinoid, clothianidin (CLTD) and the pyrethroid deltamethrin (8:1 w/w) under the brand name Fludora Fusion® developed by Bayer (Bayer CropScience, Monheim, Germany) for indoor residual spraying (IRS) as a tool for insecticide resistance management (IRM) has also demonstrated its high e cacy against various malaria vectors, including pyrethroid-resistant populations 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…and An. funestus showed no increased mortality compared to pITNs (Tchouakui et al, 2023). The only other published RG study recorded that mid-low mortality levels are induced with An.…”
Section: Mortality and Sterilitymentioning
confidence: 70%
“…funestus, and An. gambiae s.s./s.l (Corbel et al, 2010;Koudou et al, 2011;Pennetier et al, 2013;Awolola et al, 2014;Ketoh et al, 2018;Oumbouke et al, 2019;Pwalia et al, 2019;Tchakounte et al, 2019;Ibrahim et al, 2020;Menze et al, 2020;Barreaux et al, 2022;Menze et al, 2022;Tchouakui et al, 2023). To confirm that the success of PBO is through direct inhibition of P450s, studies provided evidence of P450-mediated resistance through several indicators: mortality in bioassays with a preexposure to PBO; P450 activity assays; and higher frequencies of P450 allelic markers (Awolola et al, 2014;Ketoh et al, 2018;Menze et al, 2022).…”
Section: Mortality and Sterilitymentioning
confidence: 99%
See 1 more Smart Citation